1999
DOI: 10.1080/00288330.1999.9516889
|View full text |Cite
|
Sign up to set email alerts
|

Albatross predation of juvenile southern blue whiting (Micromesistius australis) on the Campbell Plateau

Abstract: Dietary samples collected at Campbell Island in summer 1997 indicate that southern blue whiting (Micromesistius australis) formed the bulk of the food of black-browed albatrosses (Diomedea melanophrys impavida) during the chick-rearing period. Birds preyed upon a single size class of fish with a mode at 80-90 mm standard length; fish were 4-5 months old and belonged to the 0+ age group. Satellite tracking showed that, when performing trips of short duration, adult albatrosses foraged within the 1000 m depth co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…(1997); 10, Hunter and Klages (1989); 11, Waugh et al . (1999); 12, Cherel et al . (1999); 13, this study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(1997); 10, Hunter and Klages (1989); 11, Waugh et al . (1999); 12, Cherel et al . (1999); 13, this study.…”
Section: Discussionmentioning
confidence: 96%
“…The fish component of the diet of Black‐browed Albatrosses is similar at the Falkland Islands and at Campbell Island, with M. australis the most important fish species. Around the Falkland Islands this fish is taken by Black‐browed Albatrosses as offal/discard from commercial fishing vessels (Thompson & Riddy 1995) but might also be caught naturally as at Campbell Island (Cherel et al . 1999); the size of M. australis eaten in these islands was similar, and much smaller than the specimens typically caught by M. australis fisheries (Cherel et al .…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, jellyfish were detected infrequently (<20% of samples) and in low volumes (<5.3% by mass; Thompson, ). The single study on Campbell albatross diet also reported gelatinous organisms as a minor prey item (<2.3% by prey mass; Cherel, Waugh, & Hanchet, ). Despite the rare occurrence in stomach content, predation of scyphozoan jellyfish has been observed visually in black‐browed albatross (Suazo, ; Weimerskirch et al., ), and stomach temperature loggers and stable isotopes used on species in the same genus indicate their consumption may be more common (Catry, Phillips, Phalan, Silk, & Croxall, ; Connan, McQuaid, Bonnevie, Smale, & Cherel, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a predator, M. australis feeds on crustacean (euphausiid and amphipods), small fishes (myctophiids), salps, cephalopods, siphonophores and other plankton groups. In turn, they act as a prey, feeding the black-browed albatross Diomedea melanophrys impavida (Cherel, Waugh, & Hanchet, 1999), rock-hopper penguin Eudypes chrysocome (Cherel et al, 1999), kingclip Genypterus blacodes (Dunn, Connell, Forman, Stevens, & Horn, 2010), southern hake M. australis and other species of sharks and rays.…”
Section: Discussionmentioning
confidence: 99%